2018
DOI: 10.21776/ub.igtj.2018.007.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dayak Onion (Eleutherine palmifolia (L) Merr. Crude Extract on Histopatology of Gills, Kidney, Liver and Muscle of Aeromonas hydrophila- Infected Carp (Cyprinus carpio)

Abstract: Carp (Cyprinus carpio) is one of important freshwater cultivated fish species in Indonesia. Aeromonas hydrophila is accounted as potential pathogenic bacteria in Carp. In this study we investigated the effectiveness of crude extract of Dayak onion (Eleutherine palmifolia (L.) Merr) for the treatment of A. hydrophila infected fish. Furthermore, alteration of histophatology of several organs, gills, kidney, liver and muscle were investigated. Crude Extract of Dayak Onion (Eleutherine palmifolia (L) Merr. (CEDO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The results are observed under a microscope to see the histology of the cells in the islets of Langerhans and the surrounding tissue, whether necrosis has occurred or not. Data was analyzed qualitatively 29 .…”
Section: Histopathology Analysismentioning
confidence: 99%
“…The results are observed under a microscope to see the histology of the cells in the islets of Langerhans and the surrounding tissue, whether necrosis has occurred or not. Data was analyzed qualitatively 29 .…”
Section: Histopathology Analysismentioning
confidence: 99%
“…Moreover, anti-quorum sensing was also exhibited by the extracts by the loss of the violet pigment violaceine in Chromobacterium violaceum. Meanwhile, the results of Maftuch et al [56] demonstrated that the E. palmifolia ethanolic bulb extract displayed anti-microbial activity against Aeromonas hydrophila-infected Cyprinus carpio through a histopathology study of gills, kidney, liver, and muscle. The treatment also significantly demonstrated wound healing properties towards the infected tissues in a dose-dependent manner.…”
Section: Anti-bacterial Propertiesmentioning
confidence: 99%
“…Environmental factors, such as for example the day length, affect bulb enlargement and taste eminence in onion [33]. In onion, light range and quality impacts bulb formation and quality [34][35][36][37][38][39][40][41]. The bulb initiation and growth of further Allium species including garlic have been shown to be influenced by day length, temperature, and carbohydrates [42,43].…”
Section: Photoperiodic Control In Bulb Enlargementmentioning
confidence: 99%